Study on the effect of severe acute malnutrition on various echocardiographic parameters of the heart - M. V., Hari Pradhaa; R., Ramanathan (International Journal of Contemporary Pediatrics, 2023)
Background: Malnutrition is a major cause for morbidity and mortality in children below 5 years of age in developing countries. According to National family health survey-5 (NFHS-5), stunting has reduced from 38.4% to 35.5%. Wasting has reduced from 21.0% to 19.3% and underweight prevalence has reduced from 35.8% to 32.1%. Acute malnutrition can lead to biochemical changes based on metabolic, hormonal and glucoregulatory mechanisms and can affect various organ systems. This study aims to determine the effect of malnutrition on various cardiac parameters by M mode echocardiography. Methods: A cross sectional observational study was conducted in 50 severe acute malnutrition children selected by convenient sampling between 6 months and 5 years of age of Government Cuddalore medical college for a period of 2 years and M mode echocardiography was done to assess various parameters of cardiac wall dimensions and cardiac mass and compared with age/body surface area specific values. Results: Among SAM children, 74% had decreased end diastolic diameter, 80% had decreased end systolic diameter and 88% had decreased posterior wall dimension. Ejection fraction and fractional shortening was in normal range for all children. 64% had decreased left ventricular mass and 56% had decreased left ventricular mass index. Conclusions: Dimensions of the heart and cardiac mass was reduced in majority of malnourished children. Systolic function of the heart was relatively preserved as demonstrated by normal ejection fraction and fractional shortening. Thus, echocardiography can serve as a valuable tool in detecting changes in cardiac structure and function in malnourished children.